(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2018)
Assessment of air pollution level of Poltava is performed by using statistical data of enterprises inventory, stationary sites and results of calculations by program EOL-2000. Assessment and correlation the results by new researches (bioindication, air pollution indexes) according to the standards of Ukraine and the world ones are performed. The possibility of performance the further project for an impact of technology-related air pollution on the environment and human health is proved. Implementation of GIS for monitoring the air pollution of Poltava is proposed. This system can be used as a model of such GIS for other similar cities. The process of occurrence of the heat-island affect over cities and its influence on the atmospheric component is described. The importance and efficiency of the comprehensive study of atmospheric air pollution in cities are proved.